VISUAL PHOTOGRAPHIC COMPOSITION WITH A DESIGN APPROACH IN VERONICA SAVER'S WORK - Martinus Eko Prasetyo (Universitas Bunda Mulia, 2023)
The progress of the world of photography in Indonesia has not only made photography a hobby, even photography has become a hobby that can produce both commercially and with prestige. Producing photographic works is not enough just to take a photo framing of an object in a sense (feeling), but an appropriate method is needed so that photography enthusiasts can practice it. This research focuses on the analysis of photographic composition through the study of composition according to